2D animation storytelling / Maizatulakmar Abd Majid - Abd Majid, Maizatulakmar (2005)
Over the years most young children learn their first knowledge from observing and listen to the word they heard around them. The parents always read a story book to their children so they can learn faster. When the kid know to read, they will read anything they see but sometimes, half of them are disHke reading. They prefer to watch cartoon. This is because the cartoon is animate and looks "ahve" and makes the children more attract to watch it. That why this project will conduct to convert manual storybook to animated format using multimedia 2D animation. Before this the children just can read the book, but by multimedia 2D animation they can see the movement of the character and Usten to the characters voice. The children can learn by listening the simple word used and they can remember it easily. One simple storybook will be choose and will be convert to animated format by using a suitable software. The researcher will use simple words that are easy to understand. From previous experience, learning from animations is usefiil for young children to increase their knowledge.